2005
DOI: 10.4049/jimmunol.174.6.3643
|View full text |Cite
|
Sign up to set email alerts
|

Pyocyanin Production byPseudomonas aeruginosaInduces Neutrophil Apoptosis and Impairs Neutrophil-Mediated Host Defenses In Vivo

Abstract: Clearance of neutrophils from inflamed sites is critical for resolution of inflammation, but pathogen-driven neutrophil apoptosis can impair host defenses. We previously showed that pyocyanin, a phenazine toxic metabolite produced by Pseudomonas aeruginosa, accelerates neutrophil apoptosis in vitro. We compared wild-type and pyocyanin-deficient strains of P. aeruginosa in a murine model of acute pneumonia. Intratracheal instillation of either strain of P. aeruginosa caused a rapid increase in bronchoalveolar l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
187
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(195 citation statements)
references
References 62 publications
7
187
1
Order By: Relevance
“…As expected, very few neutrophils were detected in the lungs of unchallenged mice. Similar to previously published data from other laboratories using the same model, [16][17][18][19] the number of neutrophils in the WT BALF reached nearly 10 6 cells/lung 8 hours after bacteria instillation and nearly 2 ϫ 10 6 cells/lung 24 hours after bacteria instillation. Myeloid-specific PTEN Ϫ/Ϫ mice showed a dramatic increase in bacteria-induced neutrophil recruitment.…”
Section: Accumulation Of Pten-null Neutrophils In Inflamed Lungs Is Esupporting
confidence: 89%
“…As expected, very few neutrophils were detected in the lungs of unchallenged mice. Similar to previously published data from other laboratories using the same model, [16][17][18][19] the number of neutrophils in the WT BALF reached nearly 10 6 cells/lung 8 hours after bacteria instillation and nearly 2 ϫ 10 6 cells/lung 24 hours after bacteria instillation. Myeloid-specific PTEN Ϫ/Ϫ mice showed a dramatic increase in bacteria-induced neutrophil recruitment.…”
Section: Accumulation Of Pten-null Neutrophils In Inflamed Lungs Is Esupporting
confidence: 89%
“…The inappropriate or premature apoptosis of neutrophils could deplete cell numbers and functions, impairing host defense and favoring bacterial persistence in infections. In this context, it has been reported that neutrophil apoptosis is accelerated and neutrophil-mediated host defense is impaired in vivo during infection with Pseudomonas aeruginosa by the action of pyocyanin, a predominant phenazine exotoxin (14). Considering their anti-apoptotic action, antimicrobial peptides (LL-37, hBD-3 and HNP-1) exert an advantageous effect on host defense against bacterial infections by prolonging the lifespan of neutrophils, major phagocytes engaged in the killing of invading bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…However, the prolonged survival of activated neutrophils in patients with the above disorders, can cause the uncontrolled release of cytotoxic metabolites and pro-inflammatory substances (i.e., reactive oxygen species and proteases), which leads to the amplification of systemic inflammation, tissue injury and organ failure (9,10). In contrast, neutrophil apoptosis can be accelerated by the Fas ligand, reactive oxygen species, immune complexes and bacterial toxins (such as Pseudomonas aeruginosa exotoxin, pyocyanin) produced at the sites of inflammation and infection (11)(12)(13)(14). The inappropriate induction of neutrophil apoptosis likely depletes neutrophil numbers and functions, thereby impairing host defense and favoring bacterial invasion and persistence.…”
Section: Introductionmentioning
confidence: 99%
“…Pyocyanin, a representative pigment produced by P. aeruginosa, targets multiple cellular functions and contributes to acute as well as chronic infections, as it has several effects such as stimulating IL-8 release (Look et al, 2005), depressing host-response and inducing apoptosis in neutrophils (Allen et al, 2005). Pyoverdin is also a virulence marker in this pathogen, it was found that pyoverdin regulates its own secretion and the secretion of other P. aeruginosa virulence factors, such as exotoxin A (Lamont et al, 2002).…”
Section: Discussionmentioning
confidence: 99%